التفكير القائم على الأمل وعلاقته بالأمن النفسي للطلبة الأيتام لدور الرعاية وغير الأيتام في المرحلة الثانوية "دراسة مقارنة" - كاظم سلمان الشمري بشرى; طرار غند ياسين (Journal of College of Education, 2019)
The study has aimed to specify the relationship between the thinking based on hope and psychological security in a sample of orphans students for nursing homes and non-orphans in the secondary stage. The study sample has consisted of (240) male and female secondary –stage students (84) orphans, 36 orphans and 36 non-orphans in the Baghdad governorate for the academic year (2018/2019). It has been applied the thinking –based hope scale prepared by Ibrahim (2014) depended on the theory of hope, Snider and scale of psychological security prepared by Shoqeer (2005), relied on Maslow . The variable of inconsistence by the method of re-thinking based on the hope (0.77) , psychological security ( 0.75) while the inconsistence of Kronbach for hope-based thinking (0,81) and psychological security (0.79). The researchers found a statistically significant correlation between scores Students on the scale of thinking based on hope and degrees based on the psychological security scale , and there are differences in the relationship between the variables according to the gender variable and for the benefit of males.